2023
DOI: 10.9734/ijecc/2023/v13i71885
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Pinoxaden Herbicide against Complex Weed Flora in Wheat (Triticum aestivum L.)

Abstract: A field experiment was conducted during rabi season (2020-21) at AICRP on Wheat, College of Agriculture, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (MP), India, to study the effect of pinoxaden on weeds and the yield of wheat. The field experiment was laid out in a randomized block design with seven treatments and replicated thrice. Treatments included applying different doses of pinoxaden at 40, 45, and 90 g a.i. ha-1, clodinafop propargyl at 90 g a.i. ha-1, sulfosulfuron at 25 g a.i. ha-1 as post-eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Phalaris minor, Medicago denticulate, Cichorium intybus, Chenopodium album, Anagalis arvensis and Convolvulus arvensis were found. Similar weed species were also reported by Sahu et al [36], Patel et al [37].…”
Section: Effect On Weedssupporting
confidence: 88%
“…Phalaris minor, Medicago denticulate, Cichorium intybus, Chenopodium album, Anagalis arvensis and Convolvulus arvensis were found. Similar weed species were also reported by Sahu et al [36], Patel et al [37].…”
Section: Effect On Weedssupporting
confidence: 88%
“…However, other weeds like, Anagalis arvensis (14%) and Chenopodium album (14%) was also present in less numbers Figure 1 show the per cent of dominant weeds in the experiential area. , Jha et al, 2014, Tanisha et al, 2022and Patel et al, 2023 also reported similar weeds in Jabalpur region.…”
Section: Associated Weed Floramentioning
confidence: 78%
“…Sustainable weed management is characterized by its reliance on a variety of weed control techniques, rather than a single approach, as seen with synthetic herbicides in conventional agriculture. Therefore, to effectively control weeds, bio-herbicides should be used in conjunction with other weed management methods (Yadav et al, 2023b;Patel et al, 2023, Singh et al, 2013aSahu et al, 2022) [198,137,164,152] . Bio herbicides that are thought to be safer and 'greener' have drawn attention, as scientific reports provide increasing evidence of their efficacy.…”
Section: Introductionmentioning
confidence: 99%